Examining Optimism, Psychosocial Risks, and Cardiovascular Health Using Life's Simple 7 Metrics in the Multi-Ethnic Study of Atherosclerosis and the Jackson Heart Study - Park, Jee Won; Dulin, Akilah J.; Needham, Belinda L.; Sims, Mario; Loucks, Eric B.; Fava, Joseph L.; Dionne, Laura A.; Scarpaci, Matthew M.; Eaton, Charles B.; Howe, Chanelle J. (Frontiers in Cardiovascular Medicine, 2021)
Background: Optimism has been shown to be positively associated with better cardiovascular health (CVH). However, there is a dearth of prospective studies showing the benefits of optimism on CVH, especially in the presence of adversities, i.e., psychosocial risks. This study examines the prospective relationship between optimism and CVH outcomes based on the Life’s Simple 7 (LS7) metrics and whether multilevel psychosocial risks modify the aforementioned relationship. Methods: We examined self-reported optimism and CVH using harmonized data from two U.S. cohorts: Multi-Ethnic Study of Atherosclerosis (MESA) and Jackson Heart Study (JHS). Modified Poisson regression models were used to estimate the relationship between optimism and CVH using LS7 among MESA participants (N=3,520) and to examine the relationship of interest based on four biological LS7 metrics (body mass index, blood pressure, cholesterol, and blood glucose) among JHS and MESA participants (N=5,541). For all CVH outcomes, we assessed for effect measure modification by psychosocial risk. Results: Among MESA participants, the adjusted risk ratio (aRR) for ideal or intermediate CVH using LS7 comparing participants who reported high or medium optimism to those with the lowest level of optimism was 1.10 (95% Confidence Interval (CI): 1.04-1.16) and 1.05 (95% CI: 0.99-1.11), respectively. Among MESA and JHS participants, the corresponding aRRs for having all ideal or intermediate (versus no poor) metrics based on the four biological LS7 metrics were 1.05 (0.98-1.12) and 1.04 (0.97-1.11), respectively. The corresponding aRRs for having lower cardiovascular risk (0-1 poor metrics) based on the four biological LS7 metrics were 1.01 (0.98-1.03) and 1.01 (0.98-1.03), respectively. There was some evidence of effect modification by neighborhood deprivation for the LS7 outcome and by chronic stress for the ideal or intermediate (no poor) metrics outcome based on the four biological LS7 metrics. Conclusion: Our findings suggest that greater optimism is positively associated with better CVH based on certain LS7 outcomes among a racially/ethnically diverse study population. This relationship may be effect measure modified by specific psychosocial risks. Optimism shows further promise as a potential area for intervention on CVH. However, additional prospective and intervention studies are needed.